1990
DOI: 10.1159/000235160
|View full text |Cite
|
Sign up to set email alerts
|

Substance P-Induced Histamine Release from Human Basophils, Skin and Lung Fragments: Effect of Nedocromil Sodium and Theophylline

Abstract: We compared histamine release induced by substance P with those obtained with classical secretagogues on human basophils, lung and skin fragments. We also tested the capacity of nedocromil sodium and theophylline to inhibit histamine release in these 3 experimental models. Substance P (10––4M) caused a noncytotoxic histamine release (about 10% of total) from basophils, lung and skin fragments. Substance P-induced histamine release was always smaller than that obtained with optimal doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…In our experimen tal conditions, it was not possible to construct a complete dose-rcsponsc curve for each subject because 3 different sccretagogucs were tested on the same blood sample. Previous studies from our labora tory have, however, shown that antihuman IgE diluted to contain 0.25 ug antibodics/ml and FMP I0-1 M were optimal concentrations for leukocyte histamine release [5]. In preliminary experiments, we first determined the concentration of venom causing maximum specific (i.c.…”
Section: Leukocyte Releasabilitymentioning
confidence: 99%
“…In our experimen tal conditions, it was not possible to construct a complete dose-rcsponsc curve for each subject because 3 different sccretagogucs were tested on the same blood sample. Previous studies from our labora tory have, however, shown that antihuman IgE diluted to contain 0.25 ug antibodics/ml and FMP I0-1 M were optimal concentrations for leukocyte histamine release [5]. In preliminary experiments, we first determined the concentration of venom causing maximum specific (i.c.…”
Section: Leukocyte Releasabilitymentioning
confidence: 99%
“…It is now increasingly recognized that, besides these classical clinical properties, theophylline and more selective PDE inhibitors have anti-inflammatory and immunomodulatory effects. Indeed several studies have demonstrated that, in vitro, xanthines have a nonspecific suppressor activity in human peripheral lymphocytes [1], inhibit eosinophil degranulation [2], inhibit histamine release from mast cells and basophils [3], and have a direct inhibitory action on human alveolar respiratory burst [4]. These anti-inflammatory and immunomodulatory effects of xanthines have also been observed in vivo in animal models and also in humans.…”
mentioning
confidence: 97%
“…Whilst traditionally theophylline has been regarded as a bronchodilator, there is now growing evidence to suggest it possesses anti-inflammatory properties even at subtherapeutic levels [9±11]. Indeed, several studies have demonstrated that xanthines may exert their anti-inflammatory and immunomodulatory effects by the inhibition of eosinophil degranulation [12], histamine release from mast cells and basophils [13] antigen-and mitogen-induced T-cell proliferation [14] and T-cell recruitment into the bronchial mucosa [10], and the generation of cytokines [15]. However, the current knowledge concerning its anti-inflammatory mechanisms remains nondefinitive.…”
mentioning
confidence: 99%